2016
DOI: 10.1128/jb.00877-15
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical Protein BB0569 Is Essential for Chemotaxis of the Lyme Disease Spirochete Borrelia burgdorferi

Abstract: The Lyme disease spirochete Borrelia burgdorferi has five putative methyl-accepting chemotaxis proteins (MCPs). In this report, we provide evidence that a hypothetical protein, BB0569, is essential for the chemotaxis of B. burgdorferi. While BB0569 lacks significant homology to the canonical MCPs, it contains a conserved domain (spanning residues 110 to 170) that is often evident in membrane-bound MCPs such as Tar and Tsr of Escherichia coli. Unlike Tar and Tsr, BB0569 lacks transmembrane regions and recogniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The current evidence has revealed that all of the chemotaxis genes in the cheA 2 cluster are required for chemotaxis [11][12][13]. In contrast, the genes in the cheW 2 cluster that have been studied (with the exception of bb0569, which encodes for an atypical MCP [14]) are not involved in chemotaxis in vitro. For instance, cheW 2 and cheY 2 mutants have a similar in vitro phenotype as the wild type with no apparent defect in chemotactic function [11,13,15,16].…”
Section: Introductionmentioning
confidence: 82%
“…The current evidence has revealed that all of the chemotaxis genes in the cheA 2 cluster are required for chemotaxis [11][12][13]. In contrast, the genes in the cheW 2 cluster that have been studied (with the exception of bb0569, which encodes for an atypical MCP [14]) are not involved in chemotaxis in vitro. For instance, cheW 2 and cheY 2 mutants have a similar in vitro phenotype as the wild type with no apparent defect in chemotactic function [11,13,15,16].…”
Section: Introductionmentioning
confidence: 82%
“…The number of chemotaxis homologs encoded in the B. burgdorferi genome is greater and far more complex than other motile pathogens, such as E. coli or S. enterica ( 13 , 14 ). Additional genes, csrA and bb0569 , influence the motility regulation of B. burgdorferi ( 58 , 59 ). Carbon storage regulator, CsrA, is involved in posttranscriptional regulation of flagellar genes and contributes to cell morphology ( 59 , 60 ).…”
Section: Morphology Motility and Chemotaxis Regulationmentioning
confidence: 99%
“…Carbon storage regulator, CsrA, is involved in posttranscriptional regulation of flagellar genes and contributes to cell morphology ( 59 , 60 ). BB0569, annotated as a hypothetical protein, has sequence similarity to MCPs and was found to localize to the poles of the borrelial cell and important for motility and chemotaxis ( 58 ). B. burgdorferi motility is regulated throughout the enzootic cycle with the distinct behavior of intermittent swimming in the tick vector that includes periods of a non-motile state relative to the persistent swimming observed in the murine host ( 44 , 61 ).…”
Section: Morphology Motility and Chemotaxis Regulationmentioning
confidence: 99%
“…Constitutive gene expression is mostly limited to the use of very strong promoters. Moreover, apart from a few exceptions ( 14 – 19 ), fluorescent protein reporters have primarily been used as gene expression reporters or as cellular stains for in vivo localization of the spirochete ( 13 ). Yet, fluorescent proteins have many more uses which have transformed the field of cell biology ( 20 ).…”
Section: Introductionmentioning
confidence: 99%